2006
DOI: 10.1897/05-647r.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of response to 17β‐estradiol and 17β‐trenbolone among three small fish species

Abstract: Three small fish species, medaka (Oryzias latipes), fathead minnow (Pimephales promelas), and zebrafish (Danio rerio), were exposed to an estrogen, 17 beta-estradiol (E2), and an androgen, 17 beta-trenbolone (TB), for 21 d under flow-through conditions to compare the susceptibility among these three small fish species to the substances. Effects on gross morphology, including secondary sex characteristics and gonadosomatic index, as well as on blood or liver vitellogenin (VTG) levels were assessed. In E2 exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 25 publications
3
84
0
1
Order By: Relevance
“…Short-term (typically 21-d) assays with adult fish are being used by regulatory authorities throughout the world as a basis for identifying EDCs (Seki et al, 2006;U.S. Environmental Protection Agency, 2007;Organisation for Economic Cooperation and Development, 2009b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Short-term (typically 21-d) assays with adult fish are being used by regulatory authorities throughout the world as a basis for identifying EDCs (Seki et al, 2006;U.S. Environmental Protection Agency, 2007;Organisation for Economic Cooperation and Development, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental Protection Agency, 2007;Organisation for Economic Cooperation and Development, 2009b). While some endocrine mechanisms are reliably detected in these assays, anti-androgens are more difficult to identify in an unambiguous fashion (Seki et al, 2006;Katsiadaki et al, 2006;Filby et al, 2007;U.S. Environmental Protection Agency, 2007;Organisation for Economic Cooperation and Development, 2009b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were unable to measure circulating estrogens in our study, since the currently available methods lack the sensitivity required for this analysis in orchiectomized male rodents. However, in vitro evidence indicates that trenbolone and its primary metabolites are relatively nonestrogenic (30), and in vivo evidence demonstrates that trenbolone induces antiestrogenic effects in oviparous species (3,16,23,32,38,53). Additionally, it has been reported that trenbolone does not undergo aromatization due to its 3-oxotriene structure (46), although conflicting reports exist regarding the influence of trenbolone on circulating estrogens in mammalian species (24,26).…”
Section: E657mentioning
confidence: 99%